Mofokeng"s contribution to black Christology and theological education in South Africa - Kukuni, Tsholofelo J. (HTS teologiese studies, 2025)
This article examines Takatso Mofokeng’s influential contributions to South African theological scholarship. It underscores the importance of his praxis-oriented approach to Christology and his dedication to socio-political justice, which enhance the relevance of contemporary theological movements addressing current challenges. Despite recognition within existing literature, there is a notable lacuna and dearth of widespread acknowledgement of Mofokeng’s scholarship across the theological spectrum. This gap can be attributed to factors such as the absence of an official biography or Festschrift in his honour. Through an integrative qualitative literature review, aimed at developing new theoretical frameworks and perspectives, this article examines Mofokeng’s theology to explore the depth of his liberation, praxis and identity theology. The findings reveal that Mofokeng’s theology offers a comprehensive framework, integrating personal, social and political dimensions of faith. His work engages with individuals’ lived experiences in their socio-political contexts, emphasising social justice and liberation for oppressed communities. Consequently, Mofokeng’s Black Christology provides a nuanced understanding of individual identity and collective struggle within South African Black Theology.Contribution: This article highlights Takatso Mofokeng’s intellectual legacy, underscoring its lasting relevance in addressing contemporary theological, social justice and liberation issues. It illustrates how Mofokeng’s Black Christology, situated within the Reformed tradition, has profoundly shaped South African theological scholarship, offering new perspectives on identity, social justice and collective struggle. Consequently, Mofokeng’s Christological framework offers a nuanced articulation of individual identity and collective struggle, positioning his theology as a critical resource within South African theological discourse and broader movements for liberation, particularly for future scholars committed to advancing Black African scholarship and contributing to the ongoing African liberation movement.